2018
DOI: 10.1530/ec-17-0323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of walking in water on gut hormone concentrations and appetite: comparison with walking on land

Abstract: The effects of water exercise on gut hormone concentrations and appetite currently remain unclear. The aim of the present study was to investigate the effects of treadmill walking in water on gut hormone concentrations and appetite. Thirteen men (mean ± s.d. age: 21.6 ± 2.2 years, body mass index: 22.7 ± 2.8 kg/m2, peak oxygen uptake (VO2peak): 49.8 ± 7.8 mL/kg per min) participated in the walking in water and on land challenge. During the study period, ratings of subjective feelings of hunger, fullness, satie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Interestingly, EI was not altered when the same exercise was completed in 33 °C or in 20 °C water [ 7 ]. More recently, Ueda and collaborators asked healthy men to cycle for 30 min at 50% of their maximal aerobic capacities once land-based and once immersed (34 °C water) [ 8 ]. In this study, hunger was lower in response to the water-based trial, without any difference in absolute postexercise EI between conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, EI was not altered when the same exercise was completed in 33 °C or in 20 °C water [ 7 ]. More recently, Ueda and collaborators asked healthy men to cycle for 30 min at 50% of their maximal aerobic capacities once land-based and once immersed (34 °C water) [ 8 ]. In this study, hunger was lower in response to the water-based trial, without any difference in absolute postexercise EI between conditions [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Ueda and collaborators asked healthy men to cycle for 30 min at 50% of their maximal aerobic capacities once land-based and once immersed (34 °C water) [ 8 ]. In this study, hunger was lower in response to the water-based trial, without any difference in absolute postexercise EI between conditions [ 8 ]. More recently, Thackray and collaborators [ 9 ] showed that 60 min of swimming increased subsequent EI compared to cycling exercise and a control session.…”
Section: Introductionmentioning
confidence: 99%